Wideband UHF and SHF long-range channel characterization - Kassem, Edward; Blumenstein, Jiří; Povalač, Aleš; Vychodil, Josef; Pospíšil, Martin; Maršálek, Roman; Hruška, Jiří (Springer Open, 2019)
This paper presents an outdoor long-range (from 315 m up to 5.3 km) fixed channel campaign for both ultra high frequency and super high frequency bands with co-polarized horizontal and vertical antenna configurations. It investigates the channel characteristics of device to device communication scenarios underlaying the 5th generation networks by providing detailed research. Both line of sight and non-line of sight measurements in 1.3 GHz and 5.8 GHz frequency bands with bandwidth up to 600 MHz were conducted. The path loss, root mean square delay spread, coherence bandwidth, and channel frequency response variation are characterized. We observed that the variation is negligible in microcell line of sight environment for both above mentioned frequencies, whereas it significantly increases with frequency in different macrocell non-line of sight environments. The distance dependency of path loss was also derived. It was observed that the root mean square delay spread decreases with frequency for both line of sight microcell and non-line of sight macrocell measurements. A dependency between the root mean square delay spread and transmitter-receiver distance in non-line of sight environments was also captured. The relation between the coherence bandwidth and the root mean square delay spread was depicted. It demonstrates an exponential function in all considered channel combinations.

This paper presents an outdoor long-range (from 315 m up to 5.3 km) fixed channel campaign for both ultra high frequency and super high frequency bands with co-polarized horizontal and vertical antenna configurations. It investigates the channel characteristics of device to device communication scenarios underlaying the 5th generation networks by providing detailed research. Both line of sight and non-line of sight measurements in 1.3 GHz and 5.8 GHz frequency bands with bandwidth up to 600 MHz were conducted. The path loss, root mean square delay spread, coherence bandwidth, and channel frequency response variation are characterized. We observed that the variation is negligible in microcell line of sight environment for both above mentioned frequencies, whereas it significantly increases with frequency in different macrocell non-line of sight environments. The distance dependency of path loss was also derived. It was observed that the root mean square delay spread decreases with frequency for both line of sight microcell and non-line of sight macrocell measurements. A dependency between the root mean square delay spread and transmitter-receiver distance in non-line of sight environments was also captured. The relation between the coherence bandwidth and the root mean square delay spread was depicted. It demonstrates an exponential function in all considered channel combinations.
Wideband UHF and SHF long-range channel characterization
Keywords: Channel model; Device to device; Line of sight; Non-line of sight; Super high frequency; Ultra high frequency; Channel model; Device to device; Line of sight; Non-line of sight; Super high frequency; Ultra high frequency